A potent luminogen with NIR-IIb excitable AIE features for ultradeep brain vascular and hemodynamic three-photon imaging. (August 2022) - Li, Jiangao; Zhang, Zhijun; Deng, Xiangquan; Xu, Zhourui; Wang, Lei; Xu, Gaixia; Wang, Ke; Wang, Dong; Tang, Ben Zhong
Abstract: Three-photon excited fluorescence microscopy (3PEFM) has emerged as a promising protocol for visualizing deep-brain vasculature and hemodynamics. However, the current situation is still far from satisfactory, due to small excitation action cross-section and short excitation wavelength of those previously reported 3PEFM luminogens. Herein, we manipulated molecular engineering by subtly regulating structural planarization/twisting to achieve ingenious integration of large three-photon absorption cross-section, high fluorescence quantum yield, ultralong near-infrared IIb excitation, and aggregation-induced emission features. The resulting molecule, namely DPCZ-BT, exhibited as high as 50.6% of fluorescence quantum yield and as large as 2.0 × 10 −81 cm 6 s 2 /photon 2 of three-photon absorption cross-section, which can be excited by 1665 nm fs laser and presents a recorded penetration depth of 1860 μm for deep-brain vascular structural imaging with high spatiotemporal resolution and signal-to-background ratio. Moreover, DPCZ-BT having good photostability and excellent biocompatibility is capable of impressively approaching 1600 μm depth in monitoring red blood cells flow velocity with extraordinary clarity for hemodynamics.